2022
DOI: 10.1111/asj.13722
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of acute heat tolerance and meat quality in three chicken breeds

Abstract: In order to breed a strain that has heat tolerance and meat productivity, the commercial red-feathered Taiwan native chickens were male (F group), and heat stress resistant strain Taiwan native chickens (Taishu-9, bred by the Taiwan Livestock Research Institute) were female (TR9 group) to hybridize to generate offspring (F9 group).Three breeds of birds (male) were conducted to compare acute heat stress and meat quality. At 12 weeks of age, TR9 group showed the significantly lowest activity of plasma creatine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Zhang et al [8] revealed alterations in the metabolic pro les of chicken breast muscle under extreme heat stress conditions, indicating changes in energy metabolism and biochemical pathways. Liang et al [9] compared acute heat tolerance and meat quality among three different chicken breeds. They found that acute heat stress had discernible impacts on meat quality parameters such as pH, color, water-holding capacity, and tenderness in the different chicken breeds, suggesting that breed differences may in uence how chickens respond to acute heat stress and the subsequent meat quality outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [8] revealed alterations in the metabolic pro les of chicken breast muscle under extreme heat stress conditions, indicating changes in energy metabolism and biochemical pathways. Liang et al [9] compared acute heat tolerance and meat quality among three different chicken breeds. They found that acute heat stress had discernible impacts on meat quality parameters such as pH, color, water-holding capacity, and tenderness in the different chicken breeds, suggesting that breed differences may in uence how chickens respond to acute heat stress and the subsequent meat quality outcomes.…”
Section: Introductionmentioning
confidence: 99%